Effectiveness of Clove Nano Biopesticides Against Mosaic Virus in Patchouli - Rita Noveriza; Tri Lestari Mardiningsih; John Nefri; Siti Riffiah (Universitas Muhammadiyah Yogyakarta, 2021)
Clove oil has the potential to suppress the development of the mosaic virus in patchouli plants, but its effectiveness in the field has not been studied. This study aimed to evaluate the effect of clove nano biopesticide on controlling patchouli mosaic disease. The research was conducted at the Manoko Experimental Garden, Bandung, West Java from March to November 2018. The patchouli used was Patchoulina-2 variety, which originated from the Seed Breeder Garden in Lembang, Bandung. This study was arranged in a Randomized Block Design (RBD), consisting of five treatments and ten replications within each treatment, with one hundred plants in each replication. The results obtained showed that nano biopesticides of citronella, clove, and commercial citronella (Asimbo) were able to reduce the incidence and intensity of mosaic diseases in patchouli plants, showing the efficacy levels of 14.68%, 9.06%, and 5.83%, respectively. The application of citronella and clove biopesticides on Patchoulina-2 every month could increase plant fresh weight, when compared to the plants without treatment. Patchoulina-2 plants treated with nano biopesticides of clove and commercial citronella (Asimbo) showed higher value of fresh weight compared to those treated with citronella nano biopesticide. The clove nano biopesticide can also be developed to control mosaic diseases in patchouli plants.